Comparison of Ultrasound-guided Bilateral Anterior Quadratus Lumborum Block at the Lateral Supra-arcuate Ligament with Conventional Epidural Block in Patients Undergoing Laparoscopic Radical Gastrectomy: A Randomized Controlled Study - Liangqing Lin; Yaohua Yu; Pinhui Ke; Lili Liu; Qinghua Wu; Qingshui Lin (Journal of Medical Ultrasound)
Background: To test the novel ultrasound (US)-guided bilateral anterior quadratus lumborum block (QLBA) at the lateral supra-arcuate ligament (supra-LAL) technique combined with postoperative intravenous analgesia was a viable alternative approach of conventional thoracic epidural analgesia (TEA) for laparoscopic radical gastrectomy (LRG). Methods: Three hundred and four patients scheduled for LRG were randomized 1:1 into QLBA group: receiving a novel pathway of US-guided bilateral QLBA at the supra-LAL before general anesthesia (GA) and patient-controlled intravenous analgesia (PCIA) after surgery, and TEA group: receiving TEA before GA and patient-controlled epidural analgesia following surgery. The difference in procedure time between the treatment groups was set as the primary endpoint. Results: Compared to TEA, procedure time was significantly shorter in the QLBA group (13.19 ± 0.78 vs. 15.65 ± 3.49, P = 0.001). At 5–10 min after block, QLBA group achieved more dermatomes coverage of cold sensory block with both P < 0.001 and less influence on mean artery pressure. Intraoperative consumption of propofol and remifentanil were comparable between the two groups (1116.21 ± 199.76 vs. 1166.45 ± 125.31 ug, P = 0.245 and remifentanil 1.83 ± 0.41 vs. 1.81 ± 0.37 ng, P = 0.988). However, the QLBA group was associated with less intraoperative consumption of norepinephrine and atropine, shorter time to urinary catheter removal, and out-of-bed activity. No significant difference in extubation time, pain scores at rest and exercising across all time points postoperation was observed between two groups. Conclusion: Compared with conventional TEA, the novel technique combined with PCIA was an equivalent effective multimodal analgesic protocol for LRG. There were some advantages of technical simplicity with shorter procedure time, wider anesthetized dermatomes, less influence on intraoperative hemodynamic variables, fewer postoperative adverse events, and improved several sensible parameters of postoperative recovery. Trial Registration: The study was registered in the Chinese Clinical Trial Registry on November 02, 2022 (ChiCTR2200065325).